USE OF DIGITAL TECHNOLOGIES IN ORGANIZING LESSON PROCESSES - Mansur Mamirov; Dilbar Gulboyeva (European Science Publishing, 2024)
The issue of organization of lesson processes in the environment of digital transformation was considered on the example of general secondary education lessons, and the problems of organization and management of the educational process.
Keywords: strategy, management, digitization, technology, digital transformation.